Proportion of contextual effects in the treatment of fibromyalgia - a meta-analysis of randomised controlled trials - Whiteside, Nicola; Sarmanova, Aliya; Chen, Xi; Zou, Kun (Springer, 2017)
Objectives: To examine the proportion of the total treatment effect that is attributable to contextual effects in randomised controlled trials (RCTs) of treatments for fibromyalgia. Methods: A systematic literature search was undertaken in Medline, Web of Science, EMBASE, Cumulative Index to Nursing and Allied Health Literature (CINAHL), and Allied and Complementary Medicine in September 2015. The proportion of contextualeffect (PCE) was calculated by dividing the improvement in the placebo arm by the improvement in the treatment arm. The measure was log-transformed for each trial and the random effects model was used to pool data. The primary outcome was pain. Secondary outcomes were fibromyalgia impact questionnaire (FIQ) total and fatigue. Heterogeneity was quantified using I2. Publication bias was assessed using a funnel plot and Egger's test. Subgroup analysis was undertaken to explore heterogeneity and potential determinants of the PCE. Results: 51 eligible trials (9599 participants) were identified. The PCE was 0.60 (95% CI0·56 to 0·64) for pain, 0·57 (95% CI 0·53 to 0·61) for FIQ total, and 0·63 (95% CI 0·59 to 0·68) for fatigue. The I2 was 99.4% for pain, 99.2% for FIQ total, and 97.6% for fatigue. Conclusion: More than half of the treatment effect in fibromyalgia RCTs results from non-specific contextual factors. Reporting the total treatment effect and the proportion of contextual effect in trials may help to better translate research evidence into clinical practice.